Befristete und andere "atypische" Beschäftigungsverhältnisse: Wird der Arbeitsmarkt funktionsfähiger? - Bernhard Boockmann; Tobias Hagen (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– The impact of atypical employment on the ability of the labour market to function depends on how it is used. In this paper we first define three motives for the use of atypical employment: adjustment to fluctuations in business activity, improvement of personnel selection by extending probationary periods, and substitution of permanent employment in order to cut costs. We discuss what efficiency effects these types of usage have. When examined theoretically, it is possible to cite not only efficiency gains but also efficiency losses for each motive. For fixed-term contracts, the most common form of atypical employment in Germany, we use individual data at firm and individual level to examine the extent to which the usage in Germany corresponds with these motives for using atypical employment, and what evidence there is of the efficiency effects. The results point first to the function of personnel selection. These points are also discussed with regard to temporary work via employment agencies, legal self-employment and marginal part-time jobs. Here clear differences emerge in the reasons for using different forms of atypical employment.
Keywords: 330; atypische Beschäftigung; befristeter Arbeitsvertrag; Leiharbeit; Randbelegschaft; Probezeit; Entlassungen; Kosten; Personalauswahl; IAB-Betriebspanel; Personalplanung; Personalpolitik - Motivation